Projetos de inovação em sustentabilidade envolvendo colaboração universidade-indústria: estudo de caso do Escalab - Thamires Luciana Braz Alves (2024)
This work discusses the innovation process that is leading to the market of chemical technologies born in universities. The description of this process was divided into five stages: research/science, intellectual property protection, opportunity assessment, scaling and proof of concept and the final stage of technology transfer or startup creation. This work uses the case of Escalab (UFMG Technology Laboratory for Sustainability) to exemplify actions within the innovation process: research and development (R&D), technological mapping, scaling and acceleration of technologies, open innovation with industries and the program “go-to-market” for inserting chemical startups into the market. Furthermore, this work presents four Escalab cases in the area of sustainability in partnership with global mining companies, environmental solutions companies and independent inventors, with the aim of developing new technologies and/or products. The cases are related to the development of new applications of an industrial product based on lime suspension for the steel industry (Case Grupo Lhoist), production of nitrogen fertilizers from steel ammonia discharge (Case Biosfera Environmental Solutions), electrochemical route for reuse of iron mining waste (Case Green Ferrum) and production of children's sunscreen with natural inputs from Amazonian flora (Case Kehinde Nature).